History of the International Telecommunication Union transnational techno-diplomacy from the telegraph to the Internet - Balbi, Gabriele 1979-; Fickers, Andreas 1971- (Innovation and diplomacy in modern Europe, 2020)
Information and communication technologies are networked. Exchanging information betweentwo points in a network requires both the definition of what kind of information is to beexchanged (standardization) and the definition of rules and procedures of how this informationis produced, circulated, and received (regulation). As such, processes of standardization (thenegotiation and definition of technical standards) and regimes of regulation (theirimplementation and control by a legally and/or politically recognized institution) are at theheart of techno-political diplomacy, because they involve a multitude of actors (technical,economic, and political) and arenas (platforms of negotiation) on national, international, andtransnational levels. As the term techno-diplomacy suggests, these processes are characterizedby strategic actions, and tactical maneuvers among all actors involved and generally require ahigh degree of both technical knowledge and diplomatic skills by the negotiating parties. This book aims at studying the role of one specific actor in the field of standardization andregulation of information and communication technologies, the InternationalTelecommunication Union from its origins in the mid-19th century to nowadays. In this technodiplomatic game, ITU has been indeed an actor and had a key-role in different realms such asregulations of tariffs, technological standardization and homogeneity, establishment of sharednorms, promotion and support of projects and studies for example in developing countries